Law and Consumer Protection: Study of the Scarcity of 3 kg LPG Gas Consequences of Unfair Business Competition - Muhammad Anas Arifin; Kelik Wardiono (Universitas Muhammadiyah Surakarta, 2023)
This research, which aims to describe forms of unfair business competition practices which result in a scarcity of 3kg LPG gas and protection for consumers, is based on legal research with a non-doctrinal approach. The data in this research is primary data collected through interviews with informants selected purposively , and supported by secondary data collected by literature study. Based on the results of research and discussions conducted on business actors, it was found that there were business actors who carried out unfair business competition by practicing closed agreements; as well as business actors who carry out monopolistic practices, resulting in a shortage of 3 Kg LPG Gas and causing harm to consumers.